NiZn double hydroxide nanosheet-anchored nitrogen-doped graphene enriched with the gamma-NiOOH phase as an activity modulated water oxidation electrocatalyst - Nadeema, Ayasha; Dhavale, Vishal M.; Kurungot, Sreekumar (Nanoscale, 2017)
Herein, we report a facile solvothermal process to synthesize an active electrocatalyst for the oxygen evolution reaction (OER) in an alkaline medium by anchoring nanosheets of a NiZn double hydroxide over nitrogen doped reduced graphene oxide after enriching the system with the γ-NiOOH phase. This catalyst possesses a thin, porous and open layered structure, which makes the system more efficient and accessible for a better electrochemical water oxidation reaction. Moreover, we experimentally demonstrated that incorporation of Zn via a single-step solvothermal method provides an easy approach to obtain plenty of exposed γ-NiOOH phases to make the system more viable for OER with a small overpotential of 290 mV at 10 mA cm−2 and a Tafel slope of 44 mV per decade. In addition to this, the oxophilic nature of Zn in the (Zn)Ni-LDH/N-rGO catalyst helps to improve the long-term stability of the whole system. The obtained results open up possibilities for the design of future robust OER electrocatalysts by the use of very cheap and abundant materials like Ni and Zn in place of expensive Ir and Ru in the present commercial electrocatalysts.
Keywords: catalysis; Efficient Electrocatalyst; kinetics; Metal; Nickel-Hydroxide; oxide; Oxygen Evolution Reaction; performance; XPS Spectra; zinc